A STUDI IN SILICO: POTENSI SENYAWA KATEKIN DAN TURUNANNYA DARI TEH HIJAU SEBAGAI INHIBITOR HGF SERTA PROFIL TOKSISITASNYA - Sururi, Ahmad Misbakhus; Wati, First Ambar; Maharani, Dina Kartika (Unesa Journal of Chemistry, 2023)
Green tea is a plant with a high content of catechins. Catechins are a secondary metabolites that possess many benefits and potencies, one of which is as an antitumor. This study aims to describe the potential of catechin and its derivatives as antitumor inhibitor of HGF and their toxicity profiles through in silico analysis. The ligands used in this study were catechin, gallocatechin, epicatechin, and epigallocatechin. The results showed that epicatechin has better potency (-6.6 kcal/mol) than other catechin derivatives. The toxicity characteristics of the four catechins indicate that they do not exhibit hepatotoxicity, mutagenicity, or carcinogenicity, and possess a safe LD50 value. Further studies, such as in vitro and in vivo, must reveal its potential as an antitumor HGF inhibitor.